Species identification, catch yield, fishing gear, and traditional processing of manyung fish (Ariidae) in Teluk Bintuni Regency, West Papua, Indonesia - Tadu, Daniel; Boli, Paulus; Purba, Gandi Y.S. (Universitas Sam Ratulangi, 2025)
The manyung fish, locally known as 'ikan sembilang' (family Ariidae), is a large demersal species inhabiting marine and estuarine waters, commonly found near river mouths. This study aimed to identify the species composition, catch yield, fishing gear, and traditional processing methods for manyung fish in the estuarine waters of Teluk Bintuni Regency, West Papua, Indonesia. Research was conducted from October to November 2023 at three sites: Masui and Tahiti in East Bintuni District, and SP 4 in Manimeri, West Bintuni District. A total of 49 individual fish and 15 tissue samples for DNA analysis were collected. The results identified eight distinct manyung species. The total catch yield at the respective locations was 69.64 kg, 48.56 kg, and 46.35 kg. Fishermen primarily used gillnets (locally termed 'pele') and handlines. The local community processes the catch traditionally through smoking and salting methods.